Impact of Flipped Classroom on Mathematics Learning Outcome of Senior Secondary School Students in Lagos, Nigeria - Semiu Olawale Makinde (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2020)
This study examined the impact of the flipped classroom on the learning outcome of secondary school students in mathematics in Lagos, Nigeria. It examined the impact of a flipped classroom package (FCP) on post-test performance (PP) and retention performance (RP) of students in Mathematics; it also sought to determine the influence of gender on PP and RP of students towards learning mathematics in the flipped classroom (FC). This is in response to the search for means to reverse the poor performance of students in mathematics O'level West African Secondary School Certificate Examinations. The flipped classroom, an innovative teaching technique, was introduced as a possible corrective that could produce effective student learning engagement and performance. A Quasi-experimental design was adopted and 275 Senior secondary school (SSS) 2 Students, 147experimental and 128 as control (conventional) intact classes, constituted the purposive sampled population for the study. Three research instruments: Flipped Classroom Package, Lesson Note and Performance Test were validated by expects and used for the study. The instruments were also checked for reliability; and the inter-rater reliability coefficient of a developed FC package was 0.79; lesson note, 0.83; and test instrument 0.85. Four hypotheses were raised and tested after 6 weeks of the experiment. The results of the findings indicated that the flipped classroom encourages good performance in mathematics and should, thus, be encouraged in schools for being a student centred learning approach. The study concluses among others that teachers should be encouraged to attend seminars and workshops on the use of the approach for effective performance of the learners.